EFFECTS OF BASKETBALL GAMES ON COMMON ABILITIES OF ASSOCIATES INVOLVED - Budimir Bijelić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2009)
Basketball is a sports discipline and activity distinguished by a number of advan- tages and therefore it is suitable to be included in different SPORT FOR ALL organiza- tion. This Paper has dealt with research of the effects of basketball games on certain motor and function abiliteies of associates regularly involved. 53 male associates, age 35-50, have undergone testing for seven motor variables where 2 km long walking activity (fitness index = general motor ability) mean criteria variable. Systems of predictive motr and criteria variables have been tested in complian- ce with the methodology of Eurofit battery for adults. Based on the results obtained therein and related statistical analysis it has been found that 61 % of variability for criteria variable can be explained by the system of six predictive variables: lying - rising up in sitting position; leaning up forward in sitting position; standing on one leg - "flamingo"; jumping up; hand tapping and flexible han- ging down in bending motions. This statistical effect (at the level of p =.00) has accomplished the overall system of predictive motor variables, but not a snigle variable could have any special statistical effects on criteria variable UKK-2 km